Financial Statement Analysis as a Tool to Measure Financial Health in PT Argo Pantes Tbk and PT Berlina Tbk - Muhammad Febri Adiaksal; Aditya Amanda Pane; Warsani Purnama Sari (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
The purpose of this study was to determine the level of Financial Health in PT. Argo Pantes Tbk and PT. Berlina Tbk is listed on the Indonesia Stock Exchange (IDX). Data analysis techniques are carried out using descriptive use, namely by collecting data from the company's financial statements, calculating financial data using financial ratios, analyzing financial ratios and drawing conclusions. Based on the liquidity ratio of PT. Argo Pantes Tbk and PT. Berlina Tbk experienced a decline, where the decline in liquidity ratio occurred due to the large amount of the company's current debt compared to current assets owned by the company, based on the profitability ratio of PT. Berlina Tbk. Argo Pantes Tbk and PT. Berlina Tbk's decline occurred due to the company's declining profits, based on the solvency ratio of PT. Berlina Tbk. Argo Pantes Tbk and PT. Berlina Tbk experienced an increase, this happened due to the increase in company debt every year which was not followed by company assets, and based on the ratio of activity at PT. Berlina Tbk. Argo Pantes Tbk and PT. Berlina Tbk's decline occurred due to the increase in the amount of uncollectible funds.